Tangible Service Attributes And Perceived Benefits Determine Orthodontic Patient Loyalty: Atribut Layanan Berwujud Dan Manfaat Persepsian Menentukan Loyalitas Pasien Ortodonti - Sulastri Yekti Utami Rivai; Ahmad Ikhwan Setiawan (Academia Open, 2026)
General Background Competition among dental healthcare providers requires robust patient retention strategies. Specific Background Orthodontic treatments involve substantial costs and long-term commitments, making consumer evaluations of clinical environments and brand reputation critical for continued care. Knowledge Gap Previous literature often overlooks the specific mediating mechanisms that connect physical clinical evidence and affordability to long-term behavioral intentions in specialized orthodontic settings. Aims This research analyzes how physical evidence, brand image, service quality, perceived benefits, and affordability shape consumer retention through the mediating role of satisfaction at DSmile Dental Care. Results Based on a Partial Least Squares-Structural Equation Modeling analysis of 308 active patients, all evaluated predictors positively determine satisfaction. Physical evidence serves as the strongest determinant of satisfaction (β = 0.434), while satisfaction strongly mediates the transition into long-term patient retention (β = 0.295). Brand image and perceived benefits also directly stimulate long-term retention. Novelty This study highlights that physical clinical facilities function as the primary quality signaling mechanism, surpassing mere brand reputation in establishing trust for high-involvement dental procedures. Implications Dental clinic management must prioritize tangible facility improvements, transparent cost structures, and consistent service delivery to foster sustainable patient retention and satisfaction. Highlights Physical clinical evidence serves as the strongest predictor of consumer satisfaction in orthodontic services. Satisfaction significantly mediates the relationship between service attributes and long-term consumer retention. Brand image and perceived benefits directly stimulate patient retention for high-involvement dental procedures. Keywords Patient Loyalty; Orthodontic Services; Patient Satisfaction; Service Quality; Tangible Attributes